Cardiac Diseases Causing Congestive Heart Failure in Geriatric Dogs and their Diagnostic Approaches - Abhishek Dhiman; Pradeep Sharma; Deepti Bodh; Geetanjali Singh (The Indian Veterinary Journal, 2026)
In India, congestive heart failure is a prevalent yet frequently unnoticed cause of canine fatalities. The leading contributors to CHF include conditions such as dilated cardiomyopathy, mitral valve disease, hypertrophic cardiomyopathy, and pericardial effusion. Detecting CHF in its early stages is crucial, as the majority of cases occur in senior dogs, making early diagnosis essential for improving outcomes. The present study confirmed 24 canines affected with CHF. Cases were confirmed by echocardiography, and six (n=6) healthy dogs were considered for the normal study. The data were statistically analysed and expressed as mean and SE. In the study, approximately 0.93% of the canine population were found to be affected with cardiac disorders. The prominent clinical signs recorded were ascites and exercise intolerance. Radiographs revealed frequent cases of cardiomegaly, ascites, and pericardial effusion. Echocardiographic assessments identified dilated cardiomyopathy as the leading cardiac disorder in dogs, underscoring the importance of early detection and treatment.